Nutlet micromorphological characters of Teucrium taxa (Lamiaceae) in Libya - Marzouk, Ream I.; El-Darier, Salama M.; Askar, Abdelbaset M. (Phytotaxa, 2016)
The nutlet micromorphology of 11 Teucrium taxa from Libya was examined using scanning electron microscopy (SEM). The variation in shape, color, size and ornamentation of mericarp helped for taxa discrimination. Furthermore, T. capitatum and T. polium subsp. flavovirens are reported here for the first time in Libya.